Numerical and experimental investigation of the dynamics of catenary risers and the riser-induced-damping phenomenon - Chatjigeorgiou, IK; Damy, G; Leboulluec, M (2008)
Catenary risers can be equally efficient as catenary moorings in producing damping which is subsequently offered to the floating structure. Mooring-induced-damping has been investigated adequately in the recent past. The same however is not valid as far as the contribution of risers is concerned, lt should be acknowledged that the main source of damping, i.e. the drag forces, is higher in risers than in moorings as the external diameter of the former is larger and the drag coefficients, at least assuming a Morison's formula, are comparable. Therefore, the investigation of the so called riser-induced-damping phenomenon is an interesting issue. The present work is a contribution to this direction. This is performed both numerically and experimentally. For estimating damping the method proposed by Brown and Mavrakos (1999) is followed. Thus, damping due to risers is represented by the equivalent linearized coefficient the calculation of which lies on the knowledge of the energy dissipated per cycle that is calculated with the aid of the horizontal force applied at the top of the structure. Copyright © 2008 by ASME.